A Critique of the Concerns on the Proprio Motu Powers of the ICC Prosecutor - Şehmus Kurtuluş (İstanbul Hukuk Mecmuası)
During the Rome Diplomatic Conference of Plenipotentiaries where the Rome Statute of the International Criminal Court (ICC) was drafted, the ICC Prosecutor’s powers were a matter of dispute. It was particularly the Prosecutor’s authority to investigate complaints without any referral from a State Party or the Security Council which led to serious debates among participating States. Though there was wide support for the empowerment of the Prosecutor to activate the trigger mechanism of the ICC proprio motu (on his/her own initiative), there was also strong opposition. Some States described the prosecutorial powers granted to the Prosecutor as ‘unacceptable’ due to fears such as facing politically motivated prosecutions. Though the previous two prosecutorial terms showed that fears of politicized prosecutions were far-fetched, the process of selecting the third Prosecutor of the ICC for a nine-year term commencing 16 June 2021 once again put a spotlight on the prosecutorial powers as well as on the challenges the new Prosecutor would face. The present study will first draw attention to the judicial scrutiny of the chambers of the ICC and the filtering mechanism of the Rome Statute in an attempt to allay fears that the Prosecutor’s powers may lead to politicized prosecutions. The study will then explain, in light of recent developments, why the ICC Prosecutor’s power to act proprio motu is crucial for the effective operation of the Court. In so doing, the study will mainly benefit from primary sources such as the Rome Statute of the International Criminal Court, Official Records of the Rome Conference, Reports of the Office of the Prosecutor on Preliminary Examination Activities, Decisions of the Pre-Trial Chambers, as well as the comments made by scholars thereon.